Room temperature torsional fatigue properties of an iridium: 5% tungsten alloy - Younger, A.; Whitbread, R. C. (College of Aeronautics, 1965)
Introduction Fine wires of an iridium-5% tungsten alloy have been developed as a potential material for use in springs operating at high temperatures. Their suitability for such applications will to a considerable extent depend on satisfactory fatigue properties. The Materials Department of The College of Aeronautics was approached with a view to determining these torsional fatigue properties. This report covers preliminary work into this problem, namely the torsional fatigue behaviour of 0.020 ins. diameter wires at room temperature.